1974
DOI: 10.1111/j.1529-8817.1974.tb02671.x
|View full text |Cite
|
Sign up to set email alerts
|

NITROGEN ASSIMILATION OF AN OCEANIC DIATOM IN NITROGEN‐LIMITED CONTINUOUS CULTURE1

Abstract: SUMMARY The oceanic diatom Thalassiosira pseudonana Hasle and Heimdal (formerly Cyclotella nana) was grown with 12L:12D illumination cycles in nitrogen‐limited continuous culture with a mixture of ammonium and nitrate as the N source. Measurements included, at 3 different growth rates (degrees of N limitation), cell concentration, cell carbon, nitrogen, and chlorophyll a contents, cell volume, photosynthetic carbon assimilation vs. irradiance, short‐term uptake of ammonium and nitrate vs. their ambient concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
61
3
3

Year Published

1980
1980
2002
2002

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 223 publications
(79 citation statements)
references
References 40 publications
12
61
3
3
Order By: Relevance
“…Simultaneous utilization of NH: and NO; is well documented (Collos & Lewin 1974, Eppley & Renger 1974, Bienfang 1975, Conover 1975, Caperon & Ziemann 1976, Conway 1977, Maestrini et al 1982) and our results not only demonstrate dual nitrogen substrate utilization but that NH:, NO; and urea may be taken up concurrently. As pointed out by Collos (unpubl.)…”
Section: Simultaneous Uptake Of Nitrogen Compoundssupporting
confidence: 78%
“…Simultaneous utilization of NH: and NO; is well documented (Collos & Lewin 1974, Eppley & Renger 1974, Bienfang 1975, Conover 1975, Caperon & Ziemann 1976, Conway 1977, Maestrini et al 1982) and our results not only demonstrate dual nitrogen substrate utilization but that NH:, NO; and urea may be taken up concurrently. As pointed out by Collos (unpubl.)…”
Section: Simultaneous Uptake Of Nitrogen Compoundssupporting
confidence: 78%
“…For example, the U-shaped pattern of cellular carbon and nitrogen, the linear pattern of increasing C : N, and the general trend of Chl a to increase and C : Chl a to decrease with increasing temperature were observed by Thompson et al (1992). The reduction in nitrogen and Chl a quotas accompanied by an increase in C : N and C : Chl a ratios for T. pseudonana grown either under N limitation or saturating light is also well documented (Eppley and Renger 1974;Berges and Harrison 1995;Reynolds et al 1997).…”
Section: Discussionmentioning
confidence: 80%
“…In nearly all cases there is a reasonable increase in the C/Chl-a ratio caused by a decrease of cell chlorophyll a and increase of cell carbon. Only Eppley and Renger (1974) reported a cell carbon decrease while Thomas and Dodson (1972) found changing cell carbon levels. It is remarkable that the phenomenon of CIChl-a increase appears regardless of the kind of limiting nutrient.…”
Section: R: Mean Rank Of Ratio (According To Increasing Value)mentioning
confidence: 99%
“…Steele and Baird (1962), Antia et al (1963), Coombs et al (1967), Eppley (1968), Strickland et al (1969), Hobson and Pariser (1971), Thomas and Dodson (1972) and Peny (1976) showed that deficiency of P, N and Si could lead to a considerable increase in the organic carbon to chlorophyll a ratios. Caperon and Meyer (1972), Eppley and Renger (1974) and Perry (1976) described a negative correlation between specific growth rate and the organic carbon to chlorophyll a ratio. A list of the data available is given in Table 2.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation